The heritage game : economics, policy, and practice - Peacock, Alan T., 1922-; Rizzo, Ilde. (Oxford : Oxford University Press, 2008)
Governments are increasingly involved in financing and regulating the growing demand to preserve historical treasures of the past, raising issues about the scope, content, and relevance of heritage policies. This title focuses on the impact of economic analysis in the formulation and implementation of heritage policy.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Cultural property -- Protection; Cultural property -- Protection -- Economic aspects